Clinical anatomy of superior laryngeal artery via transoral approach. Issue 3 (19th April 2022) - Jia, Junxiao; Zhang, Junbo; Zeng, Zhengang; Shen, Hong; Wang, Chengyuan; Chen, Jian; Xiao, Shuifang
Abstract: Objective: Hemorrhage is the most common complication caused by transoral laryngopharyngeal surgery. It is believed that proper management of the superior laryngeal artery (SLA), the main feeding artery for the larynx and pharynx, may reduce intra‐ and postoperative hemorrhage incidence. The aim of this study was to illustrate the anatomy of the SLA via transoral endoscopic approach. Methods: Fourteen sides of SLA from heads of seven fresh‐frozen and silicone‐injected cadavers were dissected. Transoral dissections were performed for the intra‐laryngeal segment of SLA, and transcervical dissections were performed to confirm the anatomical measurements. Results: SLA had a slightly descending course from the origin to the larynx, and there was a major branch supplying the epiglottis, named pharyngo‐epiglottic artery (PEA). Parallel with the internal superior laryngeal nerve (ISLN), SLA passed through the thyrohyoid membrane and ended into the hypopharynx. The distance from SLA to the superior horn of thyroid cartilage (SHTC) was (9.11 ± 0.58)mm on the left and (9.01 ± 0.37)mm on the right; the distance from SLA to the inferior margin of the hyoid bone (IMHB) was (2.00 ± 0.11)mm on the left and (1.95 ± 0.08)mm on the right; the distance from SLA to ISLN was (5.98 ± 0.48)mm on the left and (5.78 ± 0.36)mm on the right. No significant difference was found between bilateral sides ( p  > 0.05). Moreover, the distance from SLA to superior margin of thyroid cartilage (SMTC) was (5.52 ± 0.24)mm on the left and (5.80 ± 0.15)mm on the right. A significant difference was also found between bilateral sides ( p  = 0.03), which might suggest the SLA is located further from the SMTC on the right side. Conclusion: SHTC, SMTC, and IMHB could be regarded as anatomical landmarks to locate SLA when applying a transoral approach. Moreover, a complete understanding of the detailed anatomy of the superior laryngeal artery may improve the detection of hemostasis in transoral laryngeal or hypo‐pharyngeal surgery.